The factors affecting the duration of hospitalization in pulmonary embolism - Cebeci, Zubeyir; Dereli, Seckin; Bektas, Osman (Annals of Medical Research, 2021)
Aim: The factors affecting the duration of hospitalization in PTE were evaluated In this multicenter , retrospective study.Materials and Methods: A total of 161 patients who were diagnosed as PTE were enrolled in the study. The diagnoses of all patients were confirmed via computed tomographic pulmonary angiography (CTPA). The median duration of hospitalization was calculated as 9 days. Patients were divided into two groups. Short-stay group was consisted of patients who were hospitalized for less than 9 days while the patients who were hospitalized for more than 9 days composed the long-stay group. Result: The mean hospital stay was 7.84 days (interquartile range, 5-17 days). Concerning CTPA findings; Pulmonary thromboembolism index (%) was significantly higher in long-stay patients (52.61 ± 24 versus 38.59 ± 23, p = 0.001). In addition, right and left pulmonary artery diameter, right ventricle (RV) diameter and RV/LV ratio significantly affected the length of hospital stay. Elevated levels of BNP (516 mg/dL, 10-4694 versus 269 mg/dL, 10-1400 p = 0.014) and troponin (0.7 mg/dL, 0.1-3.7 versus 0.1 mg/dL, 0.1-3 p = 0.024) were also associated with prolonged hospital stay. Conclusions: Increased right and left pulmonary artery diameters, pulmonary artery pressure, RV diameter/LV diameter ratio and pulmonary artery diameter/aortic conus diameter ratio were found to be associated with prolonged hospital stay. The higher levels of CRP and d-dimer did not have any effect on the duration of hospitalization.The rates of bleeding did not affect the length of hospitalization, regardless of the type of treatment.
Keywords: Pulmonary embolism; duration of hospitalization; risk stratification; anticoagulation